Establishment of human induced pluripotent stem cell line BAFYi001-A from a patient with Edwards syndrome - Qingqing Yang; Simin Liu; Jing Ruan; Bo Sun; Xiaoyan Chen; Xingqiang Lai (Stem Cell Research)
Edwards’ syndrome (trisomy 18) is a genetic disorder characterized by the presence of an extra chromosome 18. A specific induced pluripotent stem cell (iPSC) line, named BAFYi001-A, was generated from the umbilical cord-derived mesenchymal stromal cells (UC-MSCs) of a patient with Edwards syndrome using an integration-free Sendai virus method. This line expresses markers for identifying undifferentiated hiPSCs, trilineage differentiation potential, and genetic fidelity in the context of trisomy 18. Therefore, this cell line serves as a reliable in vitro model for investigating the pathogenesis of Edward syndrome.